2018
DOI: 10.1186/s12915-018-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the NLRP3 inflammasome by adiponectin rescues Duchenne muscular dystrophy

Abstract: BackgroundThe hormone adiponectin (ApN) exerts powerful anti-inflammatory effects on skeletal muscle and can reverse devastating myopathies, like Duchenne muscular dystrophy (DMD), where inflammation exacerbates disease progression. The NLRP3 inflammasome plays a key role in the inflammation process, and its aberrant activation leads to several inflammatory or immune diseases. Here we investigated the expression of the NLRP inflammasome in skeletal muscle and its contribution to DMD.ResultsWe find that NLRP3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 38 publications
5
80
0
Order By: Relevance
“…While not widely studied in skeletal muscle, Boursereau et al (22) have shown that NLRP3 protein exists in skeletal muscle, and levels are induced through lipopolysaccharide stimulation. A more recent investigation suggests that that angiotensin II increases skeletal muscle NLRP3 in ammasome formation, and these events lead to mitochondrial dysfunction and muscle atrophy (23).…”
Section: Discussionmentioning
confidence: 99%
“…While not widely studied in skeletal muscle, Boursereau et al (22) have shown that NLRP3 protein exists in skeletal muscle, and levels are induced through lipopolysaccharide stimulation. A more recent investigation suggests that that angiotensin II increases skeletal muscle NLRP3 in ammasome formation, and these events lead to mitochondrial dysfunction and muscle atrophy (23).…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 promotes the cleavage of pro-IL-1β and pro-IL-18 leading to their active forms. NLRP3 was up-regulated in mdx mice but was then normalized in mdx-ApN mice, through miR-711 expression [63].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Moreover, we have recently identified a strong microRNA candidate, mir-711 for mediating the anti-inflammatory action of ApN on mouse and human skeletal muscles [62]. ApN up-regulated the expression of miR-711, which, in turn, also repressed NF-κB as well as the inflammasome complex [62,63]. Eventually, as mentioned earlier, PGC-1α is also a regulator of cellular oxidant-antioxidant homeostasis by stimulating gene expression of several antioxidant enzymes such as superoxide dismutase-2, catalase, and glutathione peroxidase [43].…”
Section: Control Of Inflammation and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that chronic muscle inflammation plays a crucial role in the pathogenesis of DMD. Specifically, anti-cytokine therapies or treatments inducing depletion of CD4, CD8 lymphocytes, neutrophils, dendritic cells or macrophages (that are all found to infiltrate necrotic muscle) significantly improved the dystrophic phenotype in vivo [13,[19][20][21][22][23][24][25][26][27]. Muscles of the mdx mouse, the most commonly used model of DMD, contain 20 times more macrophages and 7 times more dendritic cells than is found in healthy individuals [28].…”
Section: Inflammation and Immune Responses In Muscular Dystrophymentioning
confidence: 99%